Facing up to the ongoing challenge of Kaposi's sarcoma. Issue 1 (February 2015) - Robey, Rebecca C.; Bower, Mark
<x xml:space="preserve">Abstract</x> Purpose of review Kaposi's sarcoma is a mesenchymal tumour caused by infection with human herpesvirus 8, usually in the context of immunodeficiency. The global incidence of Kaposi's sarcoma rose dramatically with the outbreak of HIV and AIDS. Although the introduction of combined antiretroviral therapy (cART) has seen a dramatic decline in Kaposi's sarcoma incidence, it remains a significant burden of morbidity and mortality, especially in sub-Saharan Africa. This review considers the most recent evidence regarding the prevalence, current treatment strategies and future therapies for Kaposi's sarcoma. Recent findings In the post-cART era, the epidemiology of acquired immunodeficiency syndrome-related Karposi sarcoma (AIDS-KS) is changing, with a rising incidence in the context of immune reconstitution inflammatory syndrome, and this has important implications for cART rollout initiatives. The current best-available treatment strategies use cART either alone or in combination with systemic chemotherapy, and there is new evidence for a stage-stratified treatment algorithm to guide their use. In addition, a number of new, targeted therapies for Kaposi's sarcoma are under investigation. Summary The introduction of cART has not entirely removed the challenge of AIDS-KS. It is, however, an increasingly manageable disease, although issues of drug availability in sub-Saharan Africa remain to be addressed.